BR-319: uma análise da viabilidade econômica da recuperação dos 405 quilômetros do trecho do meio - Rosario, Bruna Lage Perez de (Brasil, 2023)
This paper presents an analysis of the economic feasibility of recovering the 405 km of the Middle Section of BR-319, a federal highway that was inaugurated in 1976, but due to government abandonment over the years, it is currently in precarious conditions of trafficability, mainly the Middle Section of the highway. Given the relevance of the economic, environmental and social aspects for the decision-making regarding this investment, this research proposes to analyze these areas by applying the Cost-Benefit Analysis methodology. After a bibliographical study of the subject, the costs considered in the research were defined, costs of the reconstruction and the maintenance of the Middle Section of the BR-319, in addition to the costs arising from environmental damage, considering a life use of 30 years for the project. Subsequently, the benefits were established, and divided into cargo and people traffic, considering the time savings in the transport of passengers and the reduction of costs in terms of transporting products from the Industrial Pole of Manaus. In the next stage of the work, the coasts and benefits, already monetized, were compared and the results were analyzed with the help of feasibility indicators, pointing to a favorable scenario for carrying out the recovery of the Middle Section of BR-319.